Chain-growth simulations of the HP model for proteins. (January 2016) - Santos, Fabricio S H; Martins, Paulo H L; Bachmann, Michael
Abstract: We consider a generalized hydrophobic-polar model for proteins on square lattices. Besides the attraction between nonbonded hydrophobic monomers, the present model also takes into account an interaction between hydrophobic and polar units. By using the pruned- enriched Rosenbluth method (PERM), we investigate a specific polymer sequence composed of 42 monomers that has been proposed to simulate the physical properties of the parallel β- helix of pectate lyase C . For each temperature, the total number of generated chains varies from 10 6 to 10 7 . Physical observables such as specific heat, total energy, end-to-end distance, radius of gyration, and the average number of hydrophobic-hydrophobic and hydrophobic-polar contacts are evaluated for different values of the ratio between the hydrophobic-hydrophobic and the hydrophobic-polar contact energies. Eventually, a pseudo-phase diagram in the space of temperature and the ratio of contact energy scales is constructed.